Lit up : one reporter, three schools, twenty-four books that can change lives - Denby, David, 1943- (Henry Holt and Company, 2016)
"Denby sat in on a tenth-grade English class in a demanding New York public school for an entire academic year, and visited other schools. He read all the stories, poems, plays, and novels that the kids were reading, and creates an impassioned portrait of charismatic teachers at work, classroom dramas large and small, and fresh and inspiring encounters with the books themselves. Lit Up is a dramatic narrative that traces awkward and baffled beginnings but also exciting breakthroughs and the emergence of pleasure in reading. Denby reaffirms the power of great teachers and the importance and inspiration of great books."--